Hydrocarbon Biogeochemical Setting of the Baffin Island Oil Spill Experimental Sites. I. Sediments - Cretney, Walter J.; Green, David R.; Fowler, Brian R.; Humphrey, Blair; Fiest, David L.; Boehm, Paul D. (ARCTIC, 1987)
A baseline for petroleum residues in the sediments of the Cape Hatt Island in arctic Canada was obtained in anticipation of controlled oil releases of the Baffin Island Oil Spill (BIOS) Project. In subtidal sediments, the existing background of petroleum residues has an upper limit in the low to sub micro g/g concentration range. Petroleum was one of a variety of sources identified, including plant paraffin waxes and combustion products. Beach sediment hydrocarbons were quantitatively and qualitatively similar to those of subtidal sediments. The hydrocarbon baseline in sediments of the BIOS study area was found to be as low as might be found anywhere on earth and therefore ideally suited to the BIOS study.Key words: BIOS, arctic marine Canada, hydrocarbon baseline, sediments Mots clés: BIOS, Arctique marin canadien, niveau de référence d'hydrocarbures, sédiments